2017
DOI: 10.1016/j.amjsurg.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The seven attributes of the academic surgeon: Critical aspects of the archetype and contributions to the surgical community

Abstract: Although alternative pathways to innovation and academic contribution also exist, the academic surgeon typically devotes years of careful observation, analysis, and iterative investigation to identify and solve challenging or unexplored clinical problems, ideally leverages resources available in academic medical centers to support these endeavors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 49 publications
0
26
0
3
Order By: Relevance
“…39 Understanding that surgeons are uniquely positioned to identify new opportunities for improving patient care and developing cures for human disease in such a model, a variety of academic surgical pathways have recently emerged. 40 These include education, ethics, global surgery, innovation, and collaborative team science.…”
Section: Inclusivity Expanded (To Medical Education and Research)mentioning
confidence: 99%
“…39 Understanding that surgeons are uniquely positioned to identify new opportunities for improving patient care and developing cures for human disease in such a model, a variety of academic surgical pathways have recently emerged. 40 These include education, ethics, global surgery, innovation, and collaborative team science.…”
Section: Inclusivity Expanded (To Medical Education and Research)mentioning
confidence: 99%
“…This might be attributed to a lack of time for surgeons to devote to research, a lack of departmental resources to support their projects, and insufficient training and mentorship for the development of academic surgery. 2 In terms of global and public health, surgical diseases are under-represented in funding and program initiatives compared, for example, with infectious diseases. 3 Hu et al documented that surgery experienced a relative decrease of about $51.7 million in research funding over a 10-year period, and this mostly affected R-awards (ie, for research projects) and K-awards (ie, for mentored research).…”
Section: Introductionmentioning
confidence: 99%
“…Scholarly activity and leadership are essential for attaining advancement in clinical academia. Recent research on the attributes of academic surgeons found dissemination of knowledge, publications, and leadership in professional organizations to be defining characteristics amongst those considered academic surgeons [ 3 ]. Much literature is available on gender differences in research funding and publication rates in surgical subspecialties, but little data exist reviewing gender equity in leadership amongst surgical organizations [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%